2020
DOI: 10.3390/ijms21197164
|View full text |Cite
|
Sign up to set email alerts
|

Early Stimulation of TREK Channel Transcription and Activity Induced by Oxaliplatin-Dependent Cytosolic Acidification

Abstract: Oxaliplatin-induced peripheral neuropathy is characterized by an acute hyperexcitability syndrome triggered/exacerbated by cold. The mechanisms underlying oxaliplatin-induced peripheral neuropathy are unclear, but the alteration of ion channel expression and activity plays a well-recognized central role. Recently, we found that oxaliplatin leads to cytosolic acidification in dorsal root ganglion (DRG) neurons. Here, we investigated the early impact of oxaliplatin on the proton-sensitive TREK potassium channels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Alterations in pH i have profound effects on nerve excitability and have been proposed as factors or co-factors of many dysfunctions in both the peripheral and central nervous systems 21,[26][27][28] . In mice DRG sensory neurons, we have shown that OHP induces early pH i alterations in vitro and in vivo that modify the activity of thermosensitive calcium-permeable TRPA1 and TRPV1 channels and potassium K2P channels 7,9 , key regulators of sensory neurons excitability 29 . This study presents novel findings on the OHP ability to alter NHE1 activity after short www.nature.com/scientificreports/ incubation times, as well as, the first measurement of the intrinsic buffering power and its pH i dependence in mice DRG neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in pH i have profound effects on nerve excitability and have been proposed as factors or co-factors of many dysfunctions in both the peripheral and central nervous systems 21,[26][27][28] . In mice DRG sensory neurons, we have shown that OHP induces early pH i alterations in vitro and in vivo that modify the activity of thermosensitive calcium-permeable TRPA1 and TRPV1 channels and potassium K2P channels 7,9 , key regulators of sensory neurons excitability 29 . This study presents novel findings on the OHP ability to alter NHE1 activity after short www.nature.com/scientificreports/ incubation times, as well as, the first measurement of the intrinsic buffering power and its pH i dependence in mice DRG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the cytosolic [H + ] in neurons is caused by the formation of neuronal hemoglobin-OHP adducts, which decrease cytosolic proton buffering capacity 8 . Moreover, the intracellular pH (pH i ) change alters the electrical properties of neurons by sensitizing TRPA1 and modulating the activity of TREK channels 7,9 . On the other hand, in addition to buffering, the steady-state pH i depends on the balance between the rate of H + production from cell metabolism and the rates of acid extrusion and acid loading via alkalizing and acidifying membrane transport systems 10,11 .…”
mentioning
confidence: 99%